Targeted Prostate Health Checks, a novel system to identify men with prostate cancer—A pilot study - Stephen Langley; Jeremy Goad; Stephanie Bell; Lee Foster; Catherine Hodges; Marc Laniado; Michele Pietrasik; Alison Rooke; Matthew Knight; Edward Bosonnet; Simon Bott (BJUI Compass)
Abstract Objectives The objective of this study is to report the pilot phase of the Targeted Prostate Health Check programme that aims to identify men in the Surrey and Sussex region who have prostate cancer and who failed to be detected during the Covid era. Subjects and methods Men aged 50 to 70, or 45 to 70 if Black or with a family history of prostate cancer, were identified from participating general practitioner (GP) records. Short message service (SMS) texts invited men to visit www.talkprostate.co.uk for information on prostate cancer and give consent to prostate‐specific antigen (PSA) checks coordinated by a third‐party virtual healthcare provider. Elevated age‐related PSA levels, or levels below age‐related thresholds but at 3 ng/mL or more, triggered referral to a rapid access urology clinic. GPs were informed of the results. Results From 1842 text messages inviting 1549 people, 544 men consented to a PSA check. From 500 phlebotomy appointments, 485 (30% of invited men) took the PSA test of whom 68 (14%) were referred with an elevated PSA. After clinical review with multiparametric magnetic resonance imaging (mp‐MRI), 22 patients underwent transperineal biopsies, and prostate cancer was detected in 18 men of whom 17 (95%) had clinically significant cancer. Conclusion Our Targeted Prostate Cancer Health Check system identifies men at risk without burdening primary care. Awareness on prostate cancer risk was raised in 1549 invited men, half of whom were further educated via the registration website. One third of invited men were checked in whom clinically significant prostate cancer was found in 3.5%.